Factors influencing information privacy concerns with social networking sites (SNS) - Ili Hawa Ahmad (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2011)
This research investigated the factors influencing information privacy concern (IPC) with Social Networking Sites (SNS) among International Islamic University Malaysia (IIUM) undergraduate students. The study adopted a cross-sectional survey research approach. The combination of Social Cognitive Theory (SCT) and Protection Motivation Theory (PMT) is used as the theoretical framework to guide the research. Target respondents were undergraduate students from four Kulliyyahs i.e. Kulliyyah of Information and Communication Technology (KICT), Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), Kulliyyah of Economics and Management Sciences (KENMS) and Kulliyyah of Engineering (KENG) in IIUM located at Gombak, Kuala Lumpur. A total of 413 questionnaires were distributed. A total number of 345 respondents returned the questionnaires and 340 were used for analysis. The study found that self-efficacy, perceived severity, perceived vulnerability and perceived response efficacy positively and significantly correlated to information privacy concern. However, perceived severity, perceived vulnerability, perceived response efficacy and gender jointly and significantly influenced information privacy concern in SNS among IIUM students. Self-efficacy, reward, students' nationality, Kulliyyah (for the programme of study) and level of study were not significant in influencing information privacy concern. Implications for research and practice were also presented.